Innovation and external evaluation of non-higher education schools in Portugal: a study based on external evaluation reports - Seabra, Filipa (2020)
answer the complex demands placed by current social dynamics. Responding to this fast-paced changing society, however, has to be a priority of educational systems. Evaluation and accountability processes have been recognized as essential mechanisms in order to validate innovation – both internally – centered on self-regulation and self-evaluation, - and externally – towards the context and society the educational institution answers to. However, external evaluation also carries a number of risks [3], which may lead schools away from innovation, and toward ‘safer’ choices in terms of a culture of performativity or an audit culture [4] [5] [6]. The current model of External School Evaluation of non-higher education schools in Portugal, which was piloted in 2018, stresses innovative practices, as they are a requirement for schools to achieve the maximum evaluation mention, and less directly since indicators related to innovative practices are included in its referential. Our communication is based on the documental analysis of the external evaluation reports produced in the current cycle of evaluation and the previous reports on the schools evaluated in this cycle, focusing on innovative practices and intending to answer the following questions: What kinds of practices are deemed as innovative in external evaluation reports? Were there mentions to innovation in those schools' previous reports? How are innovation practices promoted or hindered by the perspectives present in these reports? Fifteen such reports were analyzed by the authors (higher education teachers involved in a project concerned with external school evaluation funded by the Portuguese Foundation for Science and Technology: FCT PTDC/CEDEDG/30410/2017). Results show that there are both positive and negative remarks made about innovative practices in schools. Not all reports refer to innovative practices. Aspects considered innovative are mostly related to the domain «provision of educational service», and to a smaller extent, «leadership and management». Preliminary results show that some «innovative» practices may be reinforced by the external school evaluation reports, regardless of the overall assessment of the schools involved.